Atrial functional tricuspid regurgitation: a novel and underappreciated clinical entity - Diana-Ruxandra Florescu; Stefano Figliozzi; Andrada Guta; Stefano Vicini; Michele Tomaselli; Georgică Costinel Târtea; Octavian Istrătoaie; Gianfranco Parati; Luigi Badano; Denisa Muraru (Sciendo, 2021)
Functional or secondary tricuspid regurgitation (FTR) is a progressive disease with a significant negative impact on patient morbidity and mortality. Recently, atrial fibrillation (AF) has been recognized as a cause of FTR (with/without coexisting functional mitral regurgitation) by promoting right atrial (RA) remodeling and secondary tricuspid valve (TV) annulus dilation, even in the absence of right ventricular (RV) dilation or dysfunction. This distinct form of FTR has been called "atriogenic" or "atrial". Recent evidence suggests that the RA is an important player in FTR pathophysiology not only for patients with AF, but also for those in sinus rhythm. Preliminary reports on atrial FTR show that cardioversion with documented maintenance of sinus rhythm promotes TV annulus and RA reverse remodeling and may significantly reduce FTR severity at follow-up. Large-scale studies on the prognostic benefits of rhythm vs rate-control strategy in atrial FTR patients are needed to substantiate specific guidelines indications for this subset of patients.